Hadith #3078 - Sahih Muslim - al-Qasim Abu 'Abdur Rahman القاسم أبو عبد الرحمن ويقال بن عبد الرحم (Sahih Muslim)
I used to weave these garlands from the multicoloured wool which was with us. The Messenger of Allah (ﷺ) was in the state of non Muhrim among us, and he would do all that was lawful for a lion-Muhrim with his wife.
Grade: Sahih